2017
DOI: 10.1057/s41265-017-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

“Openness” with and without Information Technology: A Framework and a Brief History

Abstract: Over the past two decades, openness (e.g. 'open' innovation, 'open' education and 'open' strategy) has been of increasing interest for researchers and of increasing relevance to practitioners. Openness is often deeply embedded in information technology (IT) and can be both a driver for and a result of innovative IT. To clarify the concept of ''openness'', we provide an overview of the scope of cross-disciplinary research on openness. Based on this overview, we develop a framework of openness, which proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 53 publications
0
55
0
8
Order By: Relevance
“…Despite the presence of increased anonymity issues in metropolitan regions, participants confirmed a lack of transparency concerning services offered by local organizations, as well as opportunities to provide services by neighbors for neighbors along the lines of peer-support services [45]. Limited access to online platforms leads to limited access to services of local service providers and institutions, such as the police or church.…”
Section: Overall Research Context and Objectivesmentioning
confidence: 99%
“…Despite the presence of increased anonymity issues in metropolitan regions, participants confirmed a lack of transparency concerning services offered by local organizations, as well as opportunities to provide services by neighbors for neighbors along the lines of peer-support services [45]. Limited access to online platforms leads to limited access to services of local service providers and institutions, such as the police or church.…”
Section: Overall Research Context and Objectivesmentioning
confidence: 99%
“…Prior research has suggested that ESM allows information sharing and social interaction among employees within the organization [86], increasing opportunities for individuals to learn from others' experiences and knowledge [25]. Given that ESM is a type of virtual community [20], a learner's ability to directly observe others' behavior is not possible.…”
Section: Vicarious Learning In the Context Of Esmmentioning
confidence: 99%
“…Third, ESM enables learners to receive help from knowledge contributors and others. Since ESM is a communication and collaboration tool that facilitates open accessibility within organizations [25], the context of ESM allows us to study individuals' vicarious learning in modern organizations. Finally, the visibility and vicarious learning lens can offer a new perspective to understand the role of ESM in facilitating knowledge management and, in turn, an organization's ability to gain sustainable competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…breaking up exclusionary structures) [26:299]. In this framing of openness, Schlagwien et al [26] WikiTribune shares characteristics with other production communities like GitHub (a digital workspace for the production of software and nonsoftware digital artifacts [5,24]) and Wikipedia (a non-profit wiki-based global encyclopedia), however, the way in which the various open principles manifest and are enacted differ across projects. We consider WikiTribune a "hybrid" model because it is a for-profit organization that hires and manages paid professionals to produce content (unlike GitHub and Wikipedia), but also opens up the production of its product to anyone that wants to join and the consumption of its product to anyone that visits the website (unlike more traditional organizations [9]), open source development (e.g.…”
Section: Characterizing Wikitribune's Modelmentioning
confidence: 99%